The Effect of Product Quality, Price, Promotion Towards Purchase Decision and Consumer Loyalty of Tiga Serangkai Books in Riau Province - Arianto, Bambang; Zulkarnain, Zulkarnain; Samsir, Samsir (International Journal of Economic, Business & Applications, 2018)
This research conducted at PT. Tiga Serangkai in Riau province. The goal is to know the direct effect of product quality, price, and promotion to purchasing decision and consumer loyalty. The population is 369 consumers. The sample was taken as many as 192 consumers. Variables used are product quality, price, promotion of purchasing decision and loyalty. Data were analyzed using SEM (Structural Equation Modeling) analysis which operated through AMOS 20 programs. The results showed that there is influence of product quality, price and promotion to purchasing decision and consumer loyalty. But there is no positive and significant influence between promotion variable to consumer loyalty. There is a positive and significant influence between the purchase decision variable on consumer loyalty, the better the consumer purchasing decision will increase consumer loyalty consumers.